Analisis Kinerja Protokol Routing OSPF dan EIGRP Untuk Aplikasi VoIP Pada Topologi Jaringan Mesh - Lyna Dwi Maryati; Rakhmadhany Primananda; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
This study examined how the OSPF and EIGRP work in mesh topology for VoIP service. To determine the performace of both routing protocol, used 3 parameter of QoS, namely throughput, jitter and packet loss. Based on scenarios that have been determined, a study of OSPF and EIGRP performance for VoIP service in mesh network topology is as follows : In EIGRP routing protocol the value of throughput codec g729 is between 40-50 kbps on the codec g711 is 7-20 kbps, the jitter value on the g711 and g729 codecs is between 200-600 seconds and the packet loss is in the 1-600 bytes range in the codec g729 , The codec g711 packet loss is worth 10000-600000 bytes, EIGRP has an average convergence time of 13-19 seconds. While on OSPF the value of throughput in g729 codec is between 30-50 kbps on g711 codec worth 18-30 kbps, jitter value on g711 and g729 codec is between 400-600 seconds and packet loss is in the range of 7-600 bytes in codec g729, In the codec g711 packet loss is worth 16000-200000 bytes, OSPF has an average convergence time of 30-50 seconds. In low communication scenario, OSPF dominant has better performance than EIGRP. In medium communication scenario, the parameters throughput, jitter and packet loss performance of EIGRP is better than OSPF. As for the time of convergence EIGPR has better performance than OSPF.